USING MAKE-A MATCH TO IMPROVE THE STUDENTS’ READING COMPREHENSION AT MTS GUPPI SAMATA GOWA - Irwanto ,; Sitti Nurpahmi (ETERNAL (English, Teaching, Learning and Research Journal), 2017)
The main objective of this study is to find out the effectiveness of students ability in Reading comprehension that taught by using Make a Match method. This research was conducted at MTs Guppi Samata Gowa Regency in Academic Year 2016/2017. In this research, the population were students in the first grade. The numbers of population were 50 students. In taking the sample, Class VII A and VII B was chosen by using purposive sampling technique.. Quasi-experimental design was applied in this research with two group pre-test and post-test design. Class VII A was chosen as controlled class by using conventional method (speech method) and Class VII B was chosen as experimental class that taught by using Make a Match method. The instrument used to collect data was reading test, especially multiple choice as a representation of reading and some vocabularies to make a matching in the translation of the words. The result of the data analysis indicated that there was a significant improvement in the students’ reading comprehension after being taught using Make a Match method. It was proved by the result of the statistical analysis of the level significance P = 0.05 with degree of freedom (df) = 48 indicated that the t-test values of the students’ reading (5.511) was higher than t-table value (2.021). Based on the result analysis, the researcher concludes that of using Make a Match method was effective to improve reading comprehension at the first grade students’ of MTs Guppi Samata Gowa, because make a match have some advantages such as each students can be directly involved in answering a question given to them in the from a card, secondly, it can increase the students’ activity. Thirdly, it can help avoid students being bored during teaching learning process and make a match method can motivate and encourage students to be more interested and enthusiastic in learning English.